Tinjauan Hukum Kewenangan Pemerintah Daerah dalam Pengelolaan Aset Daerah - Yusmad, Muammar Arafat (Maddika : Journal of Islamic Family Law, 2017)
The government through regional instruments seeks the management of local assets in order to generate profit for development financing. Currently, it is still found that the management of local assets is not neglected and becomes the burden of APBD every year. Many factors are causing regional assets not well managed, such as the overlapping of local asset management authority and unprofessional management of regional assets by private companies. This study aims to analyze the juridical aspects of the management of regional assets in accordance with the duties and authorities of local government. In conclusion: The regulation on  local assets management and legal protection has not been optimal. The obscurity arrangement of local asset management and  unequivocal sanctions resulted in the management of regional assets that should have added to the potential of the Regional Revenue (PAD), it becomes a burden for the region itself